THE MAIN GUIDELINES OF ECOLOGICALLY ORIENTED INNOVATIVE ACTIVITY IN THE HOUSING AND COMMUNAL SERVICES SECTOR - Andrey (Вестник университета)
The present article deals with the analysis of negative influence of the housing and communal services sector on the environment along with the main guidelines of decreasing this influence. The author suggests the following guidelines of work: improving the legal basis, economical guideline which means search for mutually beneficial conditions for businessmen and dwellers so that it might increase the profitability of waste recycling, ecological education aimed at the development of active civilian position and national consciousness within different age groups; various forms of work in this direction are enumerated, innovative guideline itself supposing implementation of ecologically oriented innovative development aimed at sustainable development and search for the equilibrium system of ecological and economical development of the country.